Delivering on EU food safety and nutrition in 2050 - future challenges and policy preparedness - Mylona, Kalliopi; Maragkoudakis, Petros; Bock, Anne-Katrin; Wollgast, Jan; Caldeira, Sandra Louro; Ulberth, Franz (Pulication Office of the European Union, 2016)
The report focuses on nutrition and food safety policy in European Union and on future development. Intended for professional public.
JRC science for policy report, ISSN 1018-5593
Keywords: výživová politika; nutriční nároky; Nutrition Policy; zdravotnické plánování; veřejné zdravotnictví; Europe; Food Safety; Health Planning; Evropa; Evropská unie; Nutritional Requirements; bezpečnost potravin; politologie, politika, zdravotní politika; European Union; nutriční terapie, dietoterapie a výživa